1997
DOI: 10.1002/cite.330691103
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich verschiedener verfahrenstechnischer Konzepte der präparativen Flüssigchromatographie

Abstract: Liquid chromatography utilising porous solid phases (adsorption chromatography) is one of the most powerful and versatile methods of modern analytical chemistry. Its widespread application is due in part to the development of a broad range of combinations of solid stationary and liquid mobile phase. Normal phase and reverse phase chromatography with pure and chemically modified silica gel, respectively, affinity chromatography, and ion chromatography can be cited as examples [1]. In addition to its use as an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Further on, it could be experimentally shown, that the separation performance of annular and batch chromatography is comparable [5], enabling a simple scaleup from small batch columns to larger annular chromatographs. In case of dominating equilibrium and mass transfer effects, but negligible dispersion, it was also theoretically shown that the separation performance regarding productivity, yield and specific solvent consumption, is the same for both processes [11,12].…”
Section: Introductionmentioning
confidence: 94%
“…Further on, it could be experimentally shown, that the separation performance of annular and batch chromatography is comparable [5], enabling a simple scaleup from small batch columns to larger annular chromatographs. In case of dominating equilibrium and mass transfer effects, but negligible dispersion, it was also theoretically shown that the separation performance regarding productivity, yield and specific solvent consumption, is the same for both processes [11,12].…”
Section: Introductionmentioning
confidence: 94%
“…The production rate of the rotating cylindrical annulus is comparable to that of the BCR [9]. The rotating annulus can be considered as a number of batch columns arranged in a circle and periodically charged with feed.…”
Section: Batch Chromatographic Reactor (Bcr)mentioning
confidence: 99%
“…A distinction is made between models that take Vol. 9 Chromatographic Reactorsmass transfer resistance into account and models in which equilibrium between the solid and the fluid phase is assumed. By employing the model of axial dispersion, axial mixing along the column can be described.…”
Section: Modeling Of Chromatographic Reactorsmentioning
confidence: 99%
“…by repeated injections or recycling chromatography, but in any case the disadvantages of product dilution and discontinuous operation remain [1][2][3]. Continuous techniques can be classifi ed into those where the inlets and outlets are fi xed whereas the stationary phase is moved and the ones where the inlets and outlets are moved along the stationary phase (see Fig.…”
Section: From Elution Chromatography To Countercurrent Chromatographymentioning
confidence: 99%